A New and Efficient One‐Pot Synthesis of 2‐Fluoroalkyl Substituted Indoles. (20th November 2014) - Wang, Zengxue; Ma, Qingwen
Abstract : A new simple and efficientone‐pot synthesis of 2‐fluoroalkyl substituted indoles from 2‐aminobenzyl alcohols with fluorine‐containingcarboxylic acids in the presence of Ph3 P, CCl4, and NEt3 is described. Various kinds of 2‐fluoroalkyl substituted indole derivatives can be conveniently prepared. Abstract :